Negative Regulation of TGFβ Signaling by the Kinase LKB1 and the Scaffolding Protein LIP1 - Morén, Anita (American Society for Biochemistry and Molecular Biology, 2011)
Signal transduction by the Smad pathway elicits critical biological responses to many extracellular polypeptide factors, including TGFβ and bone morphogenetic protein. Regulation of Smad signaling imparts several cytoplasmic and nuclear mechanisms, some of which entail protein phosphorylation. Previous work established a protein complex between Smad4 and the scaffolding protein LKB1-interacting protein 1 (LIP1). LKB1 is a well studied tumor suppressor kinase that regulates cell growth and polarity. Here, we analyzed the LKB1-LIP1 and the Smad4-LIP1 protein complexes and found that LIP1 can self-oligomerize. We further demonstrate that LKB1 is capable of phosphorylating Smad4 on Thr(77) of its DNA-binding domain. LKB1 inhibits Smad4 from binding to either TGFβ- or bone morphogenetic protein-specific promoter sequences, which correlates with the negative regulatory effect LKB1 exerts on Smad4-dependent transcription. Accordingly, LKB1 negatively regulates TGFβ gene responses and epithelial-mesenchymal transition. Thus, LKB1 and LIP1 provide negative control of TGFβ signaling.